2020
DOI: 10.2147/cmar.s244527
|View full text |Cite
|
Sign up to set email alerts
|

<p>CircRNA Circ_0001721 Promotes the Progression of Osteosarcoma Through miR-372-3p/MAPK7 Axis</p>

Abstract: Background: Osteosarcoma (OS) is the most common bone tumor. Many studies have reported that circular RNAs (circRNAs) play an important role in the development of a variety of human cancers. However, the underlying mechanism of circ_0001721 in regulating osteosarcoma progression remains unknown. Materials and Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect the levels of circ_0001721, miR-372-3p, and mitogen-activated protein kinase 7 (MAPK7) in osteosarcoma tissues and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Of note, circRNAs are closely related to the development of human malignancies. For instance, circ-0001721 accelerates the development of osteosarcoma via the miR-372-3p/MAPK7 axis ( Gao et al, 2020 ), and circRNA circAGFG1 accelerates the progression of triple-negative breast cancer via regulating CCNE1, the sponge of miR-195-5p ( Yang et al, 2019 ). Circ-0072088, also known as circZFR, is a newly discovered circRNA at chr5:32379220-32388780.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, circRNAs are closely related to the development of human malignancies. For instance, circ-0001721 accelerates the development of osteosarcoma via the miR-372-3p/MAPK7 axis ( Gao et al, 2020 ), and circRNA circAGFG1 accelerates the progression of triple-negative breast cancer via regulating CCNE1, the sponge of miR-195-5p ( Yang et al, 2019 ). Circ-0072088, also known as circZFR, is a newly discovered circRNA at chr5:32379220-32388780.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of Circ_0001721 can inhibit glycolysis, proliferation, and migration of osteosarcoma cells. 95 Under the regulation of PI3K/Akt signaling pathway, the phosphorylation level of glycogen synthase kinase 3β (GSK-3β) decreases, the activity of Akt and ubiquitin ligase changes, and insulin-like growth factor I (IGF-1) Induces the expression of BNIP3, thus affecting the cell cycle and promoting tumor growth. 96 …”
Section: Circrnas In Regulating Transcription Factors Genes and Sigmentioning
confidence: 99%
“…Knockout of Circ_0001721 can inhibit glycolysis, proliferation, and migration of osteosarcoma cells. 95 Under the regulation of PI3K/Akt signaling pathway, the phosphorylation level of glycogen synthase kinase 3β (GSK-3β) decreases, the activity of Akt and ubiquitin ligase changes, and insulin-like growth factor I (IGF-1) Induces the expression of BNIP3, thus affecting the cell cycle and promoting tumor growth. 96 In addition, the abnormal expression of circRNA9953-PKN2, circRNA3706-LAMA3, circRNA5431-PRKAA1, circRNA7681-FN1, circRNA8507-LAMC2, circRNA3703-LAMA3, circRNA3341-HSP90AA1, circRNA4628-EGFR, circRNA7574-ITGA6 and circRNA8506-LAMC1 were detected in ESCC.…”
Section: Pi3k/aktmentioning
confidence: 99%
“…3 Accumulating evidence revealed that circRNAs are associated with the development of many types of cancers. Gao et al 4 reported that circRNA circ_0001721 promotes the progression of osteosarcoma through miR-372-3p/MAPK7 Axis. Fang et al 5 reported that circ_0005075 stimulates the proliferation and metastasis of glioma via downregulating SIRT1.…”
Section: Introductionmentioning
confidence: 99%